Preparation and Structural Characterization of New Photopolymerizable Transparent Aluminum-Phosphate Hybrid Materials as Resins for 3D Printing - Tayama, Gabriel Toshiaki [UNESP] (2020)
The use of a hybrid sol-gel route to prepare silicate hybrid materials and glasses through stereolithography and other photopolymerizable based additive manufacturing techniques has become a major topic. In this work, we present a new synthesis of 2-hydroxyethyl methacrylate/aluminum-phosphate hybrid materials with potential use on additive manufacturing through stereolithography (SLA). The unique sol-gel chemistry of phosphates and their strong reactivity toward metal alkoxide precursors pose special challenges toward stable sols with low solvent concentration. Here, we were able to control condensation reactions, avoiding precipitation, yielding clear and long shelf-life stable 2-hydroxyethyl methacrylate/aluminum-phosphate hybrid sols with different Al/(Al + P) ratios (from 0% up to 50%), which can be further photopolymerized, yielding transparent crack-free monolithic materials. A detailed structural study through multinuclear solid-state NMR and infrared spectroscopies showed a high polymerization degree with inorganic Aly(PO4)x-like fragments acting as cross-linkers. These cross-linked structures are sensitive to the Al/(Al + P) ratio, and an increasing aluminum concentration results in a higher degree of inorganic condensation. The organic-inorganic structures are highly interconnected resulting in homogeneous materials.